Hypomethylating Agent-Based Combination Therapies to Treat Post-Hematopoietic Stem Cell Transplant Relapse of Acute Myeloid Leukemia - Ciotti, Giulia; Marconi, Giovanni; Martinelli, Giovanni (Frontiers in Oncology, 2022)
Allogeneic hematopoietic stem cell transplantation still represents the best curative option for most patients with acute myeloid leukemia, but relapse is still dramatically high. Due to their immunologic activity and safety profile, hypomethylating agents (HMA) represent an interesting backbone for combination therapies. This review report mechanism of action, safety and efficacy data on combination strategies based on HMAs in the setting of post-allogeneic stem cell transplant relapse. Several studies highlighted how HMA and donor lymphocyte (DLI) combination may be advantageous. Combination strategy of HMC with venetoclax, possibly in association with DLI, is showing excellent results in terms of response rate, including molecular responses. Lenalidomide, despite its well-known high rates of severe graft versus host disease in post-transplant setting, is showing acceptable safety profile in association with HMA with competitive response rate. Regarding FLT3-ITD mutant AML, tyrosine kinase inhibitors and particularly sorafenib are proving promising results as monotherapy and in combination with HMA. Conversely, combination strategies with gemtuzumab ozogamicin or immune checkpoint inhibitors did not show competitive response rates and seems to be currently less attractive strategies. Associations with histone deacetylase inhibitors and IDH1/2 inhibitors represent new possible strategies that need to be better investigated.